SURAL NERVE GRAFTING FOR RADIAL NERVE INJURY IN CLOSED HUMERAL SHAFT FRACTURE: A NARRATIVE REVIEW (Asian Journal of Medical Research and Health Sciences, 2026)
Radial nerve palsy is a common complication of closed humeral shaft fractures. Although most cases recover spontaneously, 10–30% show persistent motor deficit due to traction, entrapment, or neuroma-in-continuity. When direct repair is not possible, sural nerve grafting becomes necessary to restore continuity. This review highlights the indications, surgical technique, outcomes, and limitations of sural nerve grafting specifically in radial nerve injury associated with closed humeral shaft fractures.